Understanding how participatory approaches foster innovation - Douthwaite, Boru; Beaulieu, Nathalie; Lundy, Mark M.; Peters, D. (Informa UK Limited, 2009)
Adapting through innovation is one way for rural communities to sustain and improve their livelihoods and environments. Since the 1980s research and development organizations have developed participatory approaches to foster rural innovation. This paper develops a model, called the Learning-to-Innovate (LTI) model, of four basic processes linked to decision making and learning which regulate rate and quality of innovation. The processes are: creating awareness of new opportunities; deciding to adopt; adapting and changing practice; and learning and selecting. The model is then used to analyse four participatory approaches and the model is evaluated through the quality of insights generated. It shows that, while outwardly very different, the four approaches are built from combinations of 11 strategies. Most of these strategies are aimed at providing information about new opportunities and deciding whether to adopt, and give less support to the other two processes, thus suggesting one way the four participatory approaches can be strengthened. Beyond analysing participatory approaches, the model could be used as a framework for diagnosing the health of local innovation systems and designing tailor-made approaches to strengthen them.